Studi Identifikasi Gaya Arsitektur Neo-Gotik pada Bangunan dari Era Hindia Belanda di Tomohon (Studi Kasus Gereja Katolik Hati Kudus Yesus) - Austensean Stanislaus Lumunon (Politeknik Kebangsaan, 2026)
The aim of this study is to examine the adaptation of the Neo-Gothic architectural style in historical buildings from the Dutch East Indies era, focusing on the Sacred Heart of Jesus Catholic Church in Tomohon, North Sulawesi. Originally designed for local conditions and temperate climates, the application of Neo-Gothic architecture in non-European regions poses challenges related to thermal comfort, protection against high rainfall, and building material durability. The study will identify the adaptation strategies employed for this colonial church and analyse their impact on the building's style and spatial configuration. A qualitative descriptive method with a case study approach was employed, incorporating visual observation, analysis of architectural elements, and a literature review concerning Neo-Gothic and Dutch East Indies architecture. The results show that the church buildings adapt to their surroundings through several main strategies: steeply sloping roofs and wide eaves in response to high rainfall; windows that open and close to allow cross ventilation; and façade materials and colours that reflect solar radiation. These strategies have been proven to improve passive thermal comfort without compromising the symbolic and aesthetic characteristics of the Neo-Gothic architectural style. This research confirms that adapting neo-Gothic architecture to its surroundings is not merely a technical compromise, but a process that produces a distinctive form that is aesthetically pleasing. These findings are expected to inform the development of building designs, particularly places of worship in high-altitude tropical regions prone to disasters. This is particularly relevant in the context of applying neo-Gothic architectural principles to non-European climates.